Shift to Fatty Substrate Utilization in Response to Sodium-Glucose Cotransporter 2 Inhibition in Subjects Without Diabetes and Patients With Type 2 Diabetes - Ferrannini, Ele; Baldi, Simona; Frascerra, Silvia; Astiarraga, Brenno; Heise, Tim; Bizzotto, Roberto; Mari, Andrea; Pieber, Thomas R; Muscelli, Elza (Diabetes (New York, N.Y.), 2016)
Pharmacologically induced glycosuria elicits adaptive responses in glucose homeostasis and hormone release. In type 2 diabetes (T2D), along with decrements in plasma glucose and insulin levels and increments in glucagon release, sodium-glucose cotransporter 2 (SGLT2) inhibitors induce stimulation of endogenous glucose production (EGP) and a suppression of tissue glucose disposal (TGD). We measured fasting and postmeal glucose fluxes in 25 subjects without diabetes using a double glucose tracer technique; in these subjects and in 66 previously reported patients with T2D, we also estimated lipolysis (from [(2)H5]glycerol turnover rate and circulating free fatty acids, glycerol, and triglycerides), lipid oxidation (LOx; by indirect calorimetry), and ketogenesis (from circulating β-hydroxybutyrate concentrations). In both groups, empagliflozin administration raised EGP, lowered TGD, and stimulated lipolysis, LOx, and ketogenesis. The pattern of glycosuria-induced changes was similar in subjects without diabetes and in those with T2D but quantitatively smaller in the former. With chronic (4 weeks) versus acute (first dose) drug administration, glucose flux responses were attenuated, whereas lipid responses were enhanced; in patients with T2D, fasting β-hydroxybutyrate levels rose from 246 ± 288 to 561 ± 596 µmol/L (P < 0.01). We conclude that by shunting substantial amounts of carbohydrate into urine, SGLT2-mediated glycosuria results in a progressive shift in fuel utilization toward fatty substrates. The associated hormonal milieu (lower insulin-to-glucagon ratio) favors glucose release and ketogenesis.